Exploiting Cross-Luminescence in BaF2 for Ultrafast Timing Applications Using Deep-Ultraviolet Sensitive HPK Silicon Photomultipliers - Pots, Rosalinde Hendrika; Auffray, Etiennette; Gundacker, Stefan (Frontiers in Physics, 2020)
Time resolution of scintillation-based detectors is becoming continuously more important. In medical applications, especially in positron emission tomography (PET), better time of flight (TOF) information of the emitted gammas leads to a higher signal-to-noise ratio in the reconstructed image. Benefits are lower doses applied to and/or shorter scanning times for the patient. In high energy physics (HEP) ultrafast timing becomes increasingly important for reducing pile up effects in future high luminosity colliders and therefore increasing the detector sensitivity in the search for rare events and new physics. This article is an initial study on exploiting the fast cross-luminescence emission in the inorganic BaF2 scintillator with deep ultraviolet-sensitive silicon photomultipliers (SiPMs) from Hamamatsu for precise timing in PET and HEP. Using BaF2 read out by these photodetectors with a photon detection efficiency (PDE) of only about 15% in the desired 200nm emission region, a time resolution of 94±5ps FWHM is achieved when coupling with air. This figure improves to 78±4ps FWHM when coupling the BaF2 crystal with UV transparent optical grease, Viscasil, to the photodetector. This CTR performance obtained with BaF2 is already better than that measured with LYSO:Ce, a commonly used state-of-the-art inorganic scintillator in PET, when coupled to another Hamamatsu photodetector (S13360) and coupled with Meltmount. Assuming that one could increase the PDE in the ultraviolet to values of 60% obtained today at 420nm, the emission wavelength of LYSO, one could ultimately achieve CTRs below 40ps FWHM. Further improvements in CTR beyond these values could be envisaged if also the single photon time resolution (SPTR) of the ultraviolet sensitive SiPM could be enhanced. Studying the emission of BaF2 more in detail, a very fast decay component of less than 100ps has recently been observed, being of high interest in the domain of ultrafast timing. Hence, in depth investigation of this decay component would give an additional handle to improve time resolution. In view of the prospects in advancing technologies for ultraviolet sensitive SiPMs, with high PDE and SPTR, and further advancements in producing high quality BaF2, one could imagine the development of sub-30ps FWHM TOF-PET systems.